Association between NER Pathway Gene Polymorphisms and Wilms Tumor Risk - Jinhong Zhu; Wen Fu; Wei Jia; Huimin Xia; Guo-Chang Liu; Jing He (Elsevier, 2018)
Nucleotide excision repair (NER) is an essential mechanism of the body to defend against exogenous carcinogen-induced DNA damage. Defects in NER may impair DNA repair capacity and, therefore, increase genome instability and cancer susceptibility. To explore genetic predispositions to Wilms tumor, we conducted a case-control study totaling 145 neuroblastoma cases and 531 healthy controls. We systematically selected 19 potentially functional SNPs in six key genes within the NER pathway (ERCC1, XPA, XPC, XPD, XPF, and XPG). The odds ratio (OR) and 95% confidence interval (CI) were calculated to measure the strength of associations. We identified significant associations between two XPD SNPs and Wilms tumor risk. The XPD rs3810366 polymorphism significantly enhanced Wilms tumor risk (dominant model: adjusted OR = 2.12, 95% CI = 1.26-3.57). Likewise, XPD rs238406 conferred a significantly increased risk for the disease (dominant model: adjusted OR = 2.30, 95% CI = 1.40-3.80; recessive model: adjusted OR = 1.64, 95% CI = 1.11-2.44). Moreover, online expression quantitative trait locus (eQTL) analysis demonstrated that these two polymorphisms significantly affected XPD gene expression in transformed fibroblast cells. Our study provides evidence of the association between the two XPD polymorphisms and Wilms tumor risk. However, these findings warrant validation in larger studies. Keywords: nucleotide excision repair, polymorphisms, Wilms tumor, susceptibility